Phase Decomposition upon Alteration of Radiation-Damaged Monazite-(Ce) from Moss, Ostfold, Norway - Nasdala, L.; Ruschel, K.; Rhede, D.; Wirth, R.; Kerschhofer-Wallner, L.; Kennedy, Allen; Kinny, Peter; Finger, F.; Groschopf, N. (Schweizerische Chemische Gedellschaft (Swiss Chemistry Society), 2010)
The internal textures of crystals of moderately radiation-damaged monazite-(Ce) from Moss, Norway, indicate heavy, secondary chemical alteration. In fact, the cm-sized specimens are no longer mono-mineral monazite but rather a composite consisting of monazite-(Ce) and apatite pervaded by several generations of fractures filled with sulphides and a phase rich in Th, Y, and Si. This composite is virtually a 'pseudomorph' after primary euhedral monazite crystals whose faces are still well preserved. The chemical alteration has resulted in major reworking and decomposition of the primary crystals, with potentially uncontrolled elemental changes, including extensive release of Th from the primary monazite and local redeposition of radionuclides in fracture fillings. This seems to question the general alteration-resistance of orthophosphate phases in a low-temperature, 'wet' environment, and hence their suitability as potential host ceramics for the long-term immobilisation of radioactive waste.